Pengaruh Komunikasi Internal, Profesional dan Motivasi Instrinsik Terhadap Kinerja Pegawai Kejaksaan Tinggi Sulawesi Selatan - Indira Basalamah; Andi Agung Hariawan Patempoi; Yassir Yassir (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to understand and analyse the influence of internal communication, professionalism, and intrinsic motivation on the performance of employees at the South Sulawesi High Prosecutor's Office. The sample was determined using the simple random sampling technique, amounting to 86 samples. The research method employed is a survey type, and hypothesis testing was conducted using multiple linear regression analysis. The results of the study indicate that internal communication, professionalism, and intrinsic motivation have a positive and significant effect on employee performance at the South Sulawesi High Prosecutor's Office. Effective internal communication ensures that employees receive the information they need to perform their tasks well, while professionalism encourages employees to work to high standards. Intrinsic motivation, driven by personal satisfaction and achievement, strengthens employees' dedication and work spirit. The synergy of these three factors creates a conducive and productive work environment, ultimately improving employee performance and helping the organisation achieve its goals